2022
DOI: 10.3390/coatings12050669
|View full text |Cite
|
Sign up to set email alerts
|

Layer by Layer Optimization of Langmuir–Blodgett Films for Surface Acoustic Wave (SAW) Based Sensors for Volatile Organic Compounds (VOC) Detection

Abstract: Rayleigh surface acoustic wave (RSAW)-based resonant sensors, functionalized with single and multiple monomolecular layers of Langmuir–Blodgett (LB) films, were thickness and density optimized for the detection of volatile organic compounds (VOC), which could impose a serious threat on the environment and human health. Single layers of a phospholipid (SLP), hexane dissolved arachidic acid (HDAA), and chloroform dissolved arachidic acid (CDAA) were used for the LB film preparation. Several layers of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…We study the influence of the layer’s number on the morphology of the LB film of SA, and obtain evidence that the 17-layer films are optimum for sensing. This result was close to the optimum number of layers for LB film of AA reported earlier [ 17 ]. The concentration dependencies for chloroform are measured for two acoustic devices, namely, for a two-port Raleigh type SAW resonator (414 MHz) based on AT-quartz and for a SAW delay line (157.5 MHz) ST-X based on ST-quartz.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…We study the influence of the layer’s number on the morphology of the LB film of SA, and obtain evidence that the 17-layer films are optimum for sensing. This result was close to the optimum number of layers for LB film of AA reported earlier [ 17 ]. The concentration dependencies for chloroform are measured for two acoustic devices, namely, for a two-port Raleigh type SAW resonator (414 MHz) based on AT-quartz and for a SAW delay line (157.5 MHz) ST-X based on ST-quartz.…”
Section: Introductionsupporting
confidence: 91%
“…In this work, a two-port Rayleigh-type surface acoustic wave resonator (RSAW) implemented on AT, X-quartz (Eugler angles 0°, 125°, 0°) with gold electrodes and a central frequency of 414 MHz was used [ 17 ]. Figure 2 shows a schematic view (a) and an optical photo of the central part of the resonator (b) obtained by an optical confocal microscope Lext OLS5000 (Olympus Corp., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many kinds of sensors based on optical, electric, gravimetric transduction techniques, etc., have been developed for detecting VOCs [5,6]. Avramov et al presented an optimization-mass-sensitive sensor using a surface acoustic wave (SAW)-based twoport resonator as a highly sensitive quartz crystal microbalance (QCM), which exhibited excellent VOC-sensing properties [7]. Kanawade et al reported a new negative-axicon fiberoptic sensor platform, which exhibits many desirable characteristics for sensing various VOCs at room temperature [8].…”
Section: Introductionmentioning
confidence: 99%